Performance of the 2022 American College of Rheumatology/European Alliance of Associations for Rheumatology Classification Criteria for antineutrophil cytoplasmic antibody-associated vasculitis in previously diagnosed adult patients from Türkiye - Sedat Yilmaz,; Hamit Kucuk,; Merve Sungur Ozgunen,; Riza Can Kardas,; Duygu Tecer,; Ibrahim Vasi,; Muhammet Cinar,; Mehmet Akif Ozturk, (Archives of Rheumatology, 2024)
Objectives: This study aimed to evaluate the applicability of the new 2022 American College of Rheumatology (ACR)/European Alliance of Associations for Rheumatology (EULAR) criteria in Turkish adult patients previously diagnosed with antineutrophil cytoplasmic antibody-associated vasculitis (AAV). Patients and methods: One hundred sixty-four patients (96 males, 68 females; mean age: 49.6±14.4 years; range, 18 to 87 years) diagnosed with AAV by experienced rheumatologists between July 2016 and May 2022 were included in this retrospective cross-sectional study and reclassified based on the 1990 ACR criteria, the European Medicines Agency (EMEA) algorithm, and the 2022 ACR/EULAR criteria. For external validation, 83 patients (48 males, 35 females; mean age: 47.3±17.5 years; range, 19 to 81 years) diagnosed with immunoglobulin (Ig)A vasculitis were included. Results: One hundred twenty-six (76.8%) patients had granulomatosis with polyangiitis (GPA), 13 (7.9%) patients had eosinophilic granulomatosis with polyangiitis (EGPA), and 25 (15.2%) patients had microscopic polyangiitis (MPA). According to the criteria, the number of unclassified patients was nine (5.5%) for both the 2022 ACR/EULAR AAV classification criteria and the EMEA algorithm. The new criteria had an almost perfect agreement with the clinician's diagnosis (Cohen’s kappa coefficient [κ]=0.858 for GPA, κ=0.820 for EGPA, and κ=0.847 for MPA). The kappa statistics for agreement of 2022 ACR/EULAR classification criteria with the EMEA algorithm were found 0.794 for GPA, 0.820 for EGPA, and 0.700 for MPA. None of the 83 patients diagnosed with IgA vasculitis could be classified as GPA, EGPA, or MPA using the new ACR/EULAR AAV classification criteria. Conclusion: The 2022 ACR/EULAR classification criteria for AAV showed substantial or perfect agreement with the clinical diagnosis and the EMEA algorithm.